2012
DOI: 10.3109/1547691x.2012.675365
|View full text |Cite
|
Sign up to set email alerts
|

Immunological status of the progeny of breeder hens kept on ochratoxin A (OTA)- and aflatoxin B1(AFB1)-contaminated feeds

Abstract: This study aimed to evaluate the immunological status of progeny of hens kept on ochratoxin A (OTA)- and aflatoxin B(1) (AFB(1))-contaminated feed. For this purpose, White Leghorn (WL) layer breeder hens (40-weeks-of-age) were divided into six groups (A-F). Hens in Group A were fed a commercial layer ration while those in Groups B and C were kept on a diet amended with 3 and 5 mg OTA/Kg, respectively. Group D was fed a ration containing 5 mg AFB(1)/Kg, while hens in Groups E and F were kept on feed amended wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…In this paper, important decreases were observed in SRBCs, WBC, heterophil to lymphocyte ratio, and haematocrit counts (P<0.05; Table 4). Moreover, these findings are consistent with other reports, which illustrated the supportive impacts of AF on haematopoiesis and immune responses [14,16]. Our findings sustained statement of above studies, and the decrease in SRBCs and WBC counts proposed that the toxin elicited inflammatory response of the chicks [14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this paper, important decreases were observed in SRBCs, WBC, heterophil to lymphocyte ratio, and haematocrit counts (P<0.05; Table 4). Moreover, these findings are consistent with other reports, which illustrated the supportive impacts of AF on haematopoiesis and immune responses [14,16]. Our findings sustained statement of above studies, and the decrease in SRBCs and WBC counts proposed that the toxin elicited inflammatory response of the chicks [14].…”
Section: Discussionsupporting
confidence: 93%
“…The liver is considered the target organ for AF, because it is the organ where most AFs are bioactivated to the reactive 8, 9-epoxide form, known to bind DNA and proteins, damaging the liver structures and increasing the liver's weight [3]. Antibody production was suppressed against both T-dependent, such as WBC and SRBCs antigens, and that this suppression was observed during the secondary response and thus suggests a defect in the clonal expansion of antigen-specific heterophil and lymphocyte after antigen re-exposure [14]. In addition, AF exposure has been shown to reduce resistance to various bacterial, viral, and protozoan diseases in poultry [15].…”
Section: Discussionmentioning
confidence: 99%
“…In ovo AFB1-driven immunosuppression has the potential to increase the incidence of infectious disease in young poultry and negatively affect their health and productivity. Whether in ovo injection or maternal feeding, chickens exposed to AFB1 during embryogenesis have compromised cellular and humoral immune functions post hatch [160,161,211,217,218]. 1 …”
Section: Embryotoxicitymentioning
confidence: 99%
“…AFB 1 has been demonstrated to exert immunetoxic effects on cell-mediated immunity by reducing the number of circulating lymphocytes (Bondy and Pestka, 2000), or by alteration of NK cells activity and cytokine expression (Methenitou et al, 2001). AFB 1 affects immune functions and also inhibited lymphocyte blastogenesis in several animal species (Meissonier et al, 2008;Ul-Hassan et al, 2012). Silvotti et al (1997) showed a reduction in the lymphoproliferative response, a reduction of macrophage activity linked to a reduced NO production and chemotaxis in suckling piglets by sow fed with feed naturally contaminated by AFB1.…”
Section: Introductionmentioning
confidence: 99%